2020
DOI: 10.1111/ans.15988
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of three different patellar implant designs in total knee arthroplasty

Abstract: BackgroundDespite debate over the role of patellar resurfacing in total knee arthroplasty, many surgeons feel it decreases re‐operation rates and anterior pain, and an increasing number are adopting resurfacing. This study compares intra‐operative characteristics of different patellar implants to assist surgeons in gaining better understanding of these implants.MethodsThe three most commonly used patellar implants (inset, onlay round and onlay oval) were allocated randomly to 120 patients undergoing total knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“… 20 , 80 There is some disagreement in the literature regarding the clinical benefit of patella-friendly designs. 20 , 81 , 82 …”
Section: Patella Resurfacing Managementmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 , 80 There is some disagreement in the literature regarding the clinical benefit of patella-friendly designs. 20 , 81 , 82 …”
Section: Patella Resurfacing Managementmentioning
confidence: 99%
“…Gharaibeh et al compared three different designs in terms of intraoperative characteristics and patient-reported outcomes and found no difference between implants. 82 Additionally, Pavlou et al conducted a meta-analysis of 7075 cases of resurfacing and non-resurfacing TKA using both patella-friendly and non-patella-friendly designs. The authors found no difference in the incidence of reoperation or anterior knee pain between patellar-friendly and unfriendly designs regardless of resurfacing status, and concluded that prosthetic design had no effect of clinical outcome of TKA.…”
Section: Patella Resurfacing Managementmentioning
confidence: 99%
“…Inlay patellar designs are embedded into the patella after it is reamed. Onlay patellar designs are laid flat onto an evenly cut patella 53 . Inlay designs have larger bone-cement and implant-cement interfaces; however, they have not been proven to be biomechanically superior or to decrease rates of loosening 54,55 .…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Additionally, onlay designs can have either a symmetric or an asymmetric patellar component. The proposed advantage of an asymmetric onlay design is increased patellar coverage due to the native oval shape of the patella 53 . Lastly, patellar components come in a variety of thicknesses.…”
Section: Patellar Component and Positioningmentioning
confidence: 99%
“…The articular surface is formed solely by the implant dome 10 . With the use of round implants (either IN or OR), some surgeons perform a lateral facetectomy to reduce the risk of lateral compression and to improve patellar tracking 11 , 12 OO implants replicate the asymmetrical retropatellar surface, aiming to improve bone coverage and to minimize the need for patellar lateral facetectomy 10 . A recent report from the Australian Orthopaedic Association National Joint Replacement Registry (AOANJRR) 5 demonstrated lower revision rates with onlay implants compared with inlay designs.…”
mentioning
confidence: 99%